2011
DOI: 10.1007/s10824-011-9142-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence programming decisions of US symphony orchestras

Abstract: Symphony orchestra, Repertoire, Funding, Z11,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Previous research and anecdotal evidence suggested such relationships (e.g., Pierce, 2002DiMaggio 1986. Greater reliance on endowments (Endowment) may provide a SO greater autonomy and thus lower the RCI; as discussed earlier, Pompe et al (2011) concluded this. We expected that if a SO receives a larger percentage of revenue from concert revenues (Perform), a SO will perform more standard repertoire in order to draw larger audiences.…”
Section: The Model and Datamentioning
confidence: 84%
See 1 more Smart Citation
“…Previous research and anecdotal evidence suggested such relationships (e.g., Pierce, 2002DiMaggio 1986. Greater reliance on endowments (Endowment) may provide a SO greater autonomy and thus lower the RCI; as discussed earlier, Pompe et al (2011) concluded this. We expected that if a SO receives a larger percentage of revenue from concert revenues (Perform), a SO will perform more standard repertoire in order to draw larger audiences.…”
Section: The Model and Datamentioning
confidence: 84%
“…Although several of the studies discussed earlier examined the programming tendencies of SO, little consideration has been given to how funding may impact programming. The only published study that examined how funding influences SO programming found that in the 2006 season, increased funding from ticket sales, endowments, and local government increased the likelihood that a SO would perform nonstandard repertoire (Pompe et al, 2011). The study, which used a conventionality index (CI), found that federal and state government funding did not have a significant impact on programming.…”
Section: The Impact Of Funding On Symphony Orchestra Programmingmentioning
confidence: 99%
“…In the case of orchestras, they could be trying to reduce costs by simplifying their programmes, only staging a standard repertoire to ensure higher ticket sales (Pompe et al 2011), and/or reducing the number of guest artists and other high-cost performers. The results of this study show that artistic expenses by Canadian orchestras are increasing by\1 %, whereas in the US, these expenses are increasing at just over 2 %.…”
Section: Discussionmentioning
confidence: 99%
“…Pfeffer and Salancik (1978) state that organizations do not rely on the support of all of their stakeholders in order to survive, but are dependent upon those which control the most critical resources. As demonstrated by Flanagan (2012) and others (Pompe et al 2011;Hsieh 2009;Cowen 1996), arts organizations are increasingly reliant on nonperformance income.…”
Section: Resource Dependence In Arts Organizationsmentioning
confidence: 99%
See 1 more Smart Citation